Recommendations for reducing waste and bullwhip effect in Supply Chain Management (SCM) flow at a Bakery Company AA Indah (Gresik, East Java) - Iksan, Iksan; Al Khawarizmi, Ibnu Nafis (Priviet Social Sciences Journal, 2026)
Waste and information distortion exist in the supply chain management flow of bread production. Researchers have analyzed waste using value stream mapping tools and calculated the Bullwhip Effect (BE) value using the BE formula, providing improvement recommendations using failure mode effects and analysis. The identified wastes were waiting, excessive transportation, and defects. The tools used were process activity mapping (PAM) and a Supply Chain Response Matrix (SCRM). PAM analysis identified 11 operation activities, 1 transportation activity, 1 inspection activity, 1 storage activity, and 2 delay activities. Meanwhile, the day physical stock is 0.9412, with a lead time of 30 days. Based on the BE value calculation, the bread product in 2024 shows a BE value of 1.0540 for one year. Thus, demand amplification occurred for bread products in 2024. From waste identification using a cause-and-effect diagram and improvements using failure mode effects and analysis, recommendations for improving waiting time include implementing machine maintenance scheduling to prevent delays and evaluating and rearranging workflows to reduce waiting time between processes. For excessive transportation waste, the recommendations are rearranging the machine layout, optimizing goods delivery routes, implementing just-in-time methods to reduce the inventory that needs to be moved, and using technology to manage information flow more efficiently. Defect improvement recommendations include comprehensive operator training, establishment of strict work standards, use of quality checklists, application of quality management tools such as Pareto charts and 5 Why, conducting routine process evaluations, and ensuring continuous monitoring and quality control.